2021
DOI: 10.3906/sag-2101-243
|View full text |Cite
|
Sign up to set email alerts
|

Pulse steroid treatment for hospitalized adults with COVID-19

Abstract: Background/aim: High-dose steroid has been shown to reduce the mortality rate in Corona virus disease 2019 patients who need oxygen support. Here, we evaluated the effectiveness of pulse-steroid in case of unresponsiveness to treatment with high dose steroid. Materials and methods:The study is a retrospective controlled trial. We divided the patients in three groups: Standard-care therapy alone, high-dose steroid treatment (6 mg/day dexamethasone equivalent) and pulse-steroid treatment (250 mg/day methylpredn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
0
23
1
Order By: Relevance
“…Since then, there have been a number of studies comparing the two regimens with controversial results. While several studies showed similar mortality rates between PDS and NPDS regimens, 15–19 El mezzeoui et al demonstrated significantly decreased mortality in the PDS group compared to NPDS. On the contrary, Umbrello et al found that PDS was associated with increased mortality compared to NPDS.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Since then, there have been a number of studies comparing the two regimens with controversial results. While several studies showed similar mortality rates between PDS and NPDS regimens, 15–19 El mezzeoui et al demonstrated significantly decreased mortality in the PDS group compared to NPDS. On the contrary, Umbrello et al found that PDS was associated with increased mortality compared to NPDS.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequently, we excluded 1558 studies because of the following: 1391 studies used inappropriate doses of steroids or lacked the appropriate comparison, 128 studies did not report data regarding the interventions of interest, and 39 studies were excluded due to lack of the appropriate outcomes of interest. Eventually, 10 studies met our inclusion criteria and were included in the meta‐analysis 14–19,22–25 . Figure 1 shows the preferred reporting items for systematic reviews and meta‐analyses (PRISMA) flow chart that illustrates how the final studies were selected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations